Refugees and Syrian Civil War: analysis and perspectives on reception in Turkey (Tempo e Argumento, 2021)
This article examines a key issue of the Syrian Civil War: the war refugees in Turkey. In particular, the article also outlines scenarios for this refugees’ reception based on the current status of the armed conflict. Methodologically, the research is grounded on the triangulation of data that combine specialized bibliography, documents from humanitarian organizations and UNHCR information on the subject, in the light of the literature evaluating international scenarios. Turkey has been one of the countries that has welcomed Syrians since the beginning of the armed conflict in Syria in 2011. In this context, the research addresses this initiative and the challenges faced by the country due to the large number of refugees in its territory, also reflecting on the prospects for this reception. Thus, the article initially presents the definition of refugees and the contextualization of the Syrian conflict that caused the departure of many civilians. It then examines Turkey's humanitarian reception and the challenges that have arisen over years in which the conflict persists. Finally, it seeks to build three possible scenarios for the Syrian civil war and the reception of Syrian refugees.